2016
DOI: 10.12775/cjfa.2016.002
|View full text |Cite
|
Sign up to set email alerts
|

An empirical evaluation of selected accounting-based value drivers in the Polish banking sector

Abstract: The paper aims at empirical evaluation of selected accounting-based value drivers in the Polish banking sector. Using the analyses of correlation and regression, the study investigates the associations between banks' charter values, proxied by Tobin's Q, and a set of explanatory variables including size, operating efficiency, profitability, net cash flow generation capacity, leverage, asset liquidity, and risk management efficiency, each proxied by a measure based on the data available in the annual financial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Also a survey of European banks conducted by ECB [2010] revealed that proprietary valuation models used by the banks for their own purposes are based mostly on multi-stage discounted dividends or cash-flow models applied to different business lines. The empirical evidence also suggests that bank market values are driven by the relative performance measures, including ROA and ROE [Strumickas, Valančienė 2006;Bolibok 2016] and their components capturing the performance of the core banking activity [Chiou et al 2014].…”
Section: Applied Methods Of Bank Valuationmentioning
confidence: 99%
See 1 more Smart Citation
“…Also a survey of European banks conducted by ECB [2010] revealed that proprietary valuation models used by the banks for their own purposes are based mostly on multi-stage discounted dividends or cash-flow models applied to different business lines. The empirical evidence also suggests that bank market values are driven by the relative performance measures, including ROA and ROE [Strumickas, Valančienė 2006;Bolibok 2016] and their components capturing the performance of the core banking activity [Chiou et al 2014].…”
Section: Applied Methods Of Bank Valuationmentioning
confidence: 99%
“…As the value of banks is inherently dependent on the quality of their assets and risk management efficiency, numerous studies document a negative impact of impairment provisions on bank values [Strumickas and Valančienė 2006;Chiou et al 2014;CFA Institute 2014;Bolibok 2016]. In addition, Chiou et al [2014] find that larger banks are punished more severely by the capital markets for the asset impairment.…”
Section: The Value Relevance Of Accounting Variables In the Banking Smentioning
confidence: 99%